Social Movement - Saisang, Phiyaporn; Phuengpha , Noppawan (Procedia of Social Sciences and Humanities, 2024)
Social movements play an instrumental role in influencing societal change by mobilizing individuals around various issues such as human rights, environmental causes, or political reforms. This study investigates the dynamics of social movements using a quantitative approach to assess their impact on policy change, public awareness, and the mobilization of marginalized communities. Utilizing data from surveys, social media analytics, and event participation records, this research provides a comprehensive analysis of the methods employed by social movements and the outcomes they achieve.The focus of this research is on how social movements, particularly those operating in the digital age, have adapted to new communication technologies and platforms. Special attention is given to the role of social media in organizing protests and spreading awareness. By evaluating the effectiveness of various strategies employed by social movements, this study aims to quantify their influence on political processes and social structures.Findings reveal that movements employing a combination of digital mobilization and offline actions are more likely to achieve tangible policy changes. Moreover, the study finds a strong correlation between social media engagement and the rise of public awareness on key issues. The study concludes that while social movements remain powerful agents of change, their success largely depends on the ability to navigate both traditional and digital spheres effectively. The quantitative analysis offers insights into the evolving nature of collective action and its implications for social and political participation.